Surface‒functionalized, probe‒containing, polymeric nanospheres for biomedical imaging. Issue 3 (2002) - Thomas Thomas, Rhys N. Rhys N.; Guo Guo, Congyuan Congyuan
Abstract : Nanoparticles may be bound covalently to biological macromolecules for imaging, reporting, or delivery of therapeutic agents. The nanospheres of this report range from 15 nm to 30 nm in diameter, depending on the composition, although each type of nanosphere varies only ±5 nm from its mean. These nanospheres are smaller than an antibody, so may be used in the same way as other antibody labels such as enzymes in immunoassay. A double micelle forms the core of these nanospheres, in which a water pool contains approximately 1200 ionic probes such as fluorescent lanthanides, ferrite, borohydrides for BNCT, or hydrophilic therapeutic agents. Stability is imparted to the double micelle by a polymeric net that is woven into the hydrophobic zone, allowing control of diffusion. Imagable atoms may be incorporated as monomers into this polymeric net, providing as many as 200, 000 fluorine atoms for 19 F MRI or 40, 000 iodide atoms for CAT. The surfaces of the nanospheres may be tailored with hundreds of active groups such as acids or amines for later conjugation, and also polar groups such as esters, alcohols, and amino acids to suit the intended environment. The finished nanospheres may be conjugated to macromolecules using rapid, simple reactions.